Quality Control in the Subtitling Industry: An Exploratory Survey Study - Robert, Isabelle; Remael, Aline (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
Quality assurance (QA) and quality control (QC) are central to translation practice and research today, as is translation revision, which, today, is increasingly seen as an integral part of quality monitoring. Revision is also explicitly mentioned as a quality requirement in the European Standard for Translation Services EN 15 038, issued by the European Committee for Standardization (2006). Quality issues have also been a recurring topic at audiovisual translation (AVT) conferences, but in AVT, practice levels of QA and QC appear to be subject to fluctuations, and AVT research into QA and QC, including revision, is quite limited. This article will first clarify a number of terminological issues, discuss some of the relevant literature on translation and revision quality parameters and procedures, and report on a detailed survey conducted in 2013 on QA and QC practices in the subtitling industry.